Preparation and performance of catalyst for organic peroxide wastewater treatment - Zichun Yan; Haopeng Ma; Mingxia Yang (Heliyon, 2024)
To improve the oxidation pretreatment efficiency of wastewater from organic peroxides, a catalyst (CeO2-C catalyst) was developed using the calcination method with ceramic particles as the support. The crystalline structure and elemental composition of the CeO2-C catalyst were characterized by Scanning Electron Microscope (SEM), Energy Dispersive Spectrometer (EDS), and X-ray diffraction (XRD). This study explored the effects of CeO2 mass ratio, calcination temperature, and calcination time on the performance of the catalyst. The optimal preparation conditions were established through orthogonal experiments. Additionally, the synergistic effect of the catalyst on the ozone oxidation treatment of peroxide wastewater was investigated. The results indicated that the optimal preparation parameters were a CeO2 mass ratio of 4 %, a calcination temperature of 500 °C, and a duration of 5 h, respectively. After five cycles of reuse, the catalytic activity slightly decreased but remained relatively stable. With an ozone flow rate of 6 L/min, the CeO2-C/ozone catalytic oxidation process achieved a Chemical Oxygen Demand (COD) removal rate of 28.11 % in wastewater, and the B/C (the ratio of BOD concentration to COD concentration) of wastewater improved from 0.093 to 0.152. The calcination method proved effective for preparing the CeO2-C catalyst, which demonstrated significant catalytic performance and held promising application prospects in the oxidation pretreatment of organic peroxide wastewater.